Neovascular age-related macular degeneration: disease pathogenesis and current state of molecular biomarkers predicting treatment response—a scoping review - Nikolaos Dervenis; Eleftherios Agorogiannis; Panagiotis Dervenis (BMJ Open Ophthalmology)
Age-related macular degeneration is a major cause of blindness, and the development of anti-vascular endothelial growth factor (VEGF) intravitreal treatments has revolutionised the management of the disease. At the same time, new challenges and unmet needs arose due to the limitations of the current therapeutic options. Neovascularisation development during the course of the disease has a complex pathogenetic mechanism, and several biomarkers and their association with treatment outcomes have been investigated. We reviewed the relevant literature about neovascularisation development and biomarkers related to response to treatment. Improving our knowledge on the field can improve patient outcomes and offer personalised care.